German labour markets after unification - Wolfgang Franz (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1991)
This paper contains a description and analysis of the labour market in East Germany and an econometric evaluation of some effects of German unification on the West German labour market. At the outset, recent developments of employment and unemployment in East Germany are summarized together with an attempt at evaluation of the sources of joblessness. Moreover,'wage determination and wage dynamics are discussed at some length. It is investigated to what extent wage theories can contribute to an explanation of wage formation in East Germany. Finally, a macroeconometric rationing model based on the smoothing by aggregation-method is applied to obtain some educated guess estimates of effects stemming from increased imports of East Germany from West Germany for example.
Keywords: 330; Arbeitsmarkt; Deutschland; Neue Bundesländer